2003
DOI: 10.1002/cne.10800
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure and synaptic targets of tectothalamic terminals in the cat lateral posterior nucleus

Abstract: The recent appreciation of the fact that the pulvinar and lateral posterior (LP) nuclei receive two distinct types of cortical input has sparked renewed interest in this region of the thalamus. A key question is whether the primary or "driving" inputs to the pulvinar/LP complex originate in cortical or subcortical areas. To begin to address this issue, we examined the synaptic targets of tectothalamic terminals within the LP nucleus. Tectothalamic terminals were labeled using the anterograde transport of bioti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 109 publications
(118 reference statements)
4
61
0
1
Order By: Relevance
“…Likewise, for the visual system, the nature of the tectothalamic pathway from the superior colliculus to pulvinar needs to be determined: Is it a modulator of corticopulvinar-cortical pathways or a parallel visual pathway, or both? Studies in the cat (33) and monkey (34) suggest that these tectal inputs may instead drive pulvinar neurons, implying that prospective differences exist between the visual and auditory systems, and thus may belie a simple canonical principle for organizing the ascending sensory pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, for the visual system, the nature of the tectothalamic pathway from the superior colliculus to pulvinar needs to be determined: Is it a modulator of corticopulvinar-cortical pathways or a parallel visual pathway, or both? Studies in the cat (33) and monkey (34) suggest that these tectal inputs may instead drive pulvinar neurons, implying that prospective differences exist between the visual and auditory systems, and thus may belie a simple canonical principle for organizing the ascending sensory pathways.…”
Section: Discussionmentioning
confidence: 99%
“…There are also inferior collicular inputs to the medial division of the medial geniculate nucleus and spinal inputs to the posterior nucleus, raising the possibility that these, too, represent mixed first and higher order relays, but in these cases, it is not yet known if the inferior collicular or spinal inputs to these respective nuclei produce RL terminals. This possibility that these thalamic nuclei putatively identified as higher order may also contain first order relays, as seems the case for the pulvinar (Kelly et al, 2003), does not affect the main conclusion that synapses from driving (RL) ter- Wang et al (2002a). minals are relatively rare in these thalamic nuclei.…”
Section: Drivers Versus Modulatorsmentioning
confidence: 93%
“…Indeed, Kelly et al (2003) have provided clear evidence that there are RL terminals in parts of the pulvinar that are tectal in origin, indicating that the pulvinar complex may include both first and higher order relays. There are also inferior collicular inputs to the medial division of the medial geniculate nucleus and spinal inputs to the posterior nucleus, raising the possibility that these, too, represent mixed first and higher order relays, but in these cases, it is not yet known if the inferior collicular or spinal inputs to these respective nuclei produce RL terminals.…”
Section: Drivers Versus Modulatorsmentioning
confidence: 99%
“…They found that the ''collicular boutons tend to be larger and distribute to more proximal parts of the dendrites than those from the prefrontal cortex'' and that the SC inputs made asymmetric, excitatory synapses onto the thalamic neurons. While the location of these synapses has to be evaluated in comparison to other structures, such connections close to the soma have also been reported by Kelly et al (2003) in the collicular projection to the pulvinar and lateral posterior nuclei of the cat. Both the physiological and anatomical observations are consistent with the strong driving of MD by the SC and suggests that SC inputs probably have more influence on the MD relay neurons than do cortical inputs.…”
Section: Sc As a Driver Input To MDmentioning
confidence: 93%